Covid-19 Social Media Trending and Hoaxes: Malaysian Perception Index (MPI) and How Does the Law Respond to Fake News and Hoaxes (Comparing Malaysia and Indonesia) - Abu, Roziya; Sabri, Ahmad Zaharuddin Sani Ahmad; Seng, Nicholas Khoo Kim; Rodiyah, Rodiyah (Law Research Review Quarterly, 2020)
The Covid-19 pandemic hit another grim milestone on as worldwide deaths from the disease exceeded 100,000. Many countries have enforced social distancing rules and even lockdowns in an effort to contain the spread of the virus. Malaysian Government, in almost daily bases proposed initiatives and efforts to uphold Malaysia social, economic and national stability. This article deliberates an analysis on social media sentiment index by topics mentions in Malaysian government Covid19 initiatives and phenomena. This analysis was conduction with 373K mentions documented with five trending topic, two trending topics on government initiatives, one trending topic Airline Industry and one telecommunication Industry. The social media platform mentions in this study include all mentions or discussion of the topic across all public social media, Facebook, Twitter, Instagram, Forums and blogs.